PENGARUH GROSS DOMESTIC PRODUCT, INFLASI, TINGKAT SUKU BUNGA, DAN TARIF PPH BADAN TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Properti Dan Real Estate Yang Terdaftar diBEI Periode 2012-2016) - Yuli Handayani; Jeni Susyanti; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThis research was completed for some purposes : 1) to know the impact of GrossDomestic Product to the stock price, 2) to know how the inflation influences thestock price, 3) to discover what possibly happens to the stock price when theinterest rates rises, 4) to understand the correlation of PPh Tax and the stock, 5)to perceive the influence of Gross Domestic Product, inflation, interest rates, PPhTax, to the stock price.This research involves whole property and real estate companies which arelegally registered in BEI period 2012-2016. The sample selection of this researchwas using purposive sampling. According to aforementioned criteria, the totalsample was about 27 companies. The analysis method used in this research islinier regression analysis method.This research shows that there are some conclusions, those are: 1) the result of Tshows that variable of Gross Domestic Product does not have any impact to thestock price 2) the variable of inflation does not have any influence to the stockprice, 3) the variable of interest rates does not have any effect to the stock price,4) the variable of PPh Tax have correlation to the stock price, and 5) the result ofF shows that those variable of Gross Domestic Product, inflation, interest rastes,and PPh Tax impact gradually to the stock price.Key Words : Gross Domestic Product, Inflation, Interest Rates, PPh Tax, andStock Price